2016
DOI: 10.1128/jcm.02153-15
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of Phenotype in Relation to Common β-Lactam Resistance Mechanisms in Escherichia coli and Klebsiella pneumoniae

Abstract: cThe minimal concentration of antibiotic required to inhibit the growth of different isolates of a given species with no acquired resistance mechanisms has a normal distribution. We have previously shown that the presence or absence of transmissible antibiotic resistance genes has excellent predictive power for phenotype. In this study, we analyzed the distribution of six ␤-lactam antibiotic susceptibility phenotypes associated with commonly acquired resistance genes in Enterobacteriaceae in Sydney, Australia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 65 publications
0
21
1
Order By: Relevance
“…Our results showed the predominance of both Inc FIIK and FII plasmids among the isolates and their transconjugants carrying bla KPC2 and/or bla NDM1 , suggesting that these types of plasmids mediate horizontal transmission and contribute to the dissemination of bla KPC2 and/or bla NDM1 in the environment of the Egyptian hospitals, which represents a great challenge and an important factor in the dissemination of resistance and treatment failure in cases of severe infections. Agyekum et al [39] reported that FIIK is the most common plasmid replicon found in K. pneumoniae. Another study done by Al-Marzooq et al [40] reported that the most common plasmid replicons were IncR and IncL/M.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed the predominance of both Inc FIIK and FII plasmids among the isolates and their transconjugants carrying bla KPC2 and/or bla NDM1 , suggesting that these types of plasmids mediate horizontal transmission and contribute to the dissemination of bla KPC2 and/or bla NDM1 in the environment of the Egyptian hospitals, which represents a great challenge and an important factor in the dissemination of resistance and treatment failure in cases of severe infections. Agyekum et al [39] reported that FIIK is the most common plasmid replicon found in K. pneumoniae. Another study done by Al-Marzooq et al [40] reported that the most common plasmid replicons were IncR and IncL/M.…”
Section: Discussionmentioning
confidence: 99%
“…β-lactam antibiotics are among the most commonly prescribed for severe infections [80, 81] and the emergence of β-lactam resistance in K. pneumoniae has become a global health threat [82, 83]. In general, E. coli and K. pneumoniae carrying transmissible β-lactam resistance genes have predictable and normally distributed β-lactam MICs [21] but carbapenem MICs in K. pneumonia e are bimodally distributed with higher MICs correlating with OmpK36 defects [21]. OmpK36 loss or mutation is not uncommonly reported in highly resistant clinical isolates producing KPC, ESBL or AmpC β-lactamases [20, 84, 85].…”
Section: Discussionmentioning
confidence: 99%
“…Isolates were grown overnight in MHB. Bacteria were disrupted by sonication and outer membrane porins (OMPs) isolated with sarcosyl (Sigma-Aldrich, St. Louis, MO, USA), as previously described [21, 38]. Samples were boiled, analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) (12% separating gels), and stained with Imperial protein stain (Thermo Scientific, Rockford, IL, USA), following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolates resistant to 3GC or aminoglycosides were screened by multiplex PCR/reverse line blot (mPCR/RLB) (Agyekum et al., ; Ginn et al., ), to detect genes conferring resistance to β‐lactams ( bla TEM, bla SHV, bla CTX‐M, bla KPC, bla VEB, bla IMP, bla VIM, bla NDM, bla CMY‐2‐like, bla DHA, bla ACT, bla MIR, bla OXA‐10‐like, bla OXA‐30‐like, bla OXA‐48‐like genes) and aminoglycosides ( aac(3)‐II , aacA4 , aadB , armA , rmtB , rmtC , rmtF ). PCR using published primers (Ellem, Partridge, & Iredell, ; Perez‐Perez & Hanson, ; Woodford, Fagan, & Ellington, ) and sequencing was used to confirm resistance genes and determine the allele present.…”
Section: Methodsmentioning
confidence: 99%